Budgeting From an Islamic Green Economy Perspective in Local Development - Cahyani, Yutisa Tri; Santoso, Lukman; Ma'mun, Sukron (Institut Agama Islam Negeri Ponorogo, 2023)
Global climate change and environmental problems significantly threaten the Earth's ability to support human needs and well-being. This crisis is exacerbated by increased economic development activities that rely heavily on the exploitation of natural resources. Indonesia, facing similar challenges, requires the implementation of a sustainable and environmentally friendly economic model. This study examines budgeting in the context of local government budget documents and regional development reports, focusing on the integration of green economic principles in the Mataraman region of East Java, Indonesia. Using a qualitative approach, the research examines local government budget and economic development reports from Madiun City and Ponorogo Regency. It involves a comprehensive analysis of both primary and secondary sources related to local development and budgeting. The findings aim to contribute to the promotion and acceleration of green economic development in the region, thereby influencing the allocation of resources to foster an inclusive and prosperous community.